Form and Function in the Platyrrhine Skull: A Three‐Dimensional Analysis of Dental and TMJ Morphology. Issue 1 (January 2015) - Terhune, Claire E.; Cooke, Siobhán B.; Otárola‐Castillo, Erik; Terhune, Claire; Cooke, Siobhán B.; Laitman, Jeffrey T.
ABSTRACT Cranial and temporomandibular joint (TMJ) form has been shown to reflect masticatory forces and mandibular range of motion, which vary in relation to feeding strategy. Similarly, the dentition, as the portion of the masticatory apparatus most directly involved in triturating food items, strongly reflects dietary profile. Fine control over condylar and mandibular movements guides the teeth into occlusion, while the topography and position of the dental arcade mediate mandibular movements. We hypothesize that masticatory, and particularly TMJ, morphology and dental form covary in predictable ways with one another and with diet. We employed three‐dimensional geometric morphometric techniques to examine inter‐specific variation in ten platyrrhine species. Landmarks were collected on six datasets describing the upper and lower molars, cranium, glenoid fossa, mandible, and mandibular condyle; two‐block partial least squares analyses were performed to assess covariation between cranial morphology, dentition, and diet. Significant relationships were identified between the molars and the cranium, mandible, and glenoid fossa. Some of these shape complexes reflect feeding strategy; for example, higher crowned/cusped dentitions, as found in primates consuming larger quantities of structural carbohydrates (e.g., Alouatta and Saimiri), correspond to anteroposterior longer and deeper glenoid fossae. These results indicate strong covariance between dental and TMJ form, aspects of which are related to feeding behavior. However, other aspects of morphological variation display a strong phylogenetic signal; we must therefore examine further ways in which to control for phylogeny when examining covariation in interspecific masticatory form. Anat Rec, 298:29–47, 2015. © 2014 Wiley Periodicals, Inc.